A study of the prevalence and severity of vitamin D deficiency in patient with diabetic foot and its association with vascular calcification and effect on healing - Kamble, Ajonish; Swarnkar, Manish (International Surgery Journal, 2019)
Background: With the increasing prevalence of diabetes mellitus (DM), vitamin D (vit D) deficiency and vascular calcification is frequently observed in DM and is an indicator of diabetic peripheral vascular disease with variable implications. Due to the current limited understanding, this research was initiated. Aims and objective was to critically assess the prevalence and severity of vitamin D deficiency in patients with diabetic foot infection, the association between vascular calcification and vitamin D deficiency and effect on healing in diabetic foot patient with and without vitamin D deficiency. Methods: This observational study was conducted on 50 patients with diabetes mellitus. A detailed clinical history was recorded. Infection was confirmed by culture positivity and Doppler was used to detect vascular calcification. A follow-up for 3 weeks was done after which wound healing rate was assessed by change in wound surface area. Data was analyzed by Chi-square test and multivariate regression analysis. Results: 58% patients were diagnosed with vitamin D deficiency. 40% of patients found to have VC associated with DM. 100 % association of VC was found in patients with severe vitamin D deficiency. Vitamin D deficiency significantly correlated with vascular calcification (p=0.0001). A significant difference was observed in wound healing between the patients with and without vitamin D deficiency i.e. 3.14±2.04mm.sq and 4.36±1.39mm.sq. Conclusions: This study opens up an issue of recognizing vitamin D deficiency as a possible risk factor for diabetic foot infections and suggests the need for vitamin D supplementation.